Training the Public: Advancing Neoliberal Reforms Through Model Experiences. Issue 3 (4th May 2021) - Avigur-Eshel, Amit; Mandelkern, Ronen
ABSTRACT: The realisation of some neoliberal reforms depends on the public's behaviour. Given that, how do neoliberal elites operate to advance behavioural changes in the public? This question is particularly acute for neoliberals, who concurrently emphasize individuals' 'right to choose' and their obligation to 'make the right choice'. While the literature commonly focuses on either ideational persuasion or on practice-based measures (nudge), this paper identifies an additional instrument: the construction of 'model experiences' – experiences that provide common citizens with a model for their future behaviour. By constructing model experiences, neoliberal elites aim to influence mass behaviour on two interrelated levels: first, through the practical training offered by the experience itself, and second, through the wider lessons that can be conveyed to the participants who reflect on the experience. We illustrate this argument with a case study of a model experience of household financialisation: Israel's Saving for Every Child program.